Molecular Docking of Red Betel (Piper crocatum Ruiz & Pav) Bioactive Compounds as HMG-CoA Reductase Inhibitor - Bella Fatima Dora Zaelani; Mega Safithri; Dimas Andrianto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Cholesterol plaque buildup in artery walls occurs due to oxidation of Low-Density Lipoprotein (LDL) molecules by free radicals, which are a risk factor for coronary heart disease. Piper crocatum contains active compounds that can act as HMG-CoA reductase inhibitors, such as flavonoids, alkaloids, polyphenols, tannins, and essential oils. This study aimed to predict the potential of Piper crocatum extract and fraction compounds as HMG-CoA reductase inhibitors by investigating the ligand affinity to the HMG-CoA reductase enzyme. Ligand and receptor preparation was conducted using BIOVIA Discovery Studio Visualizer v16.1.0.15350 and AutoDock Tools v.1.5.6. Molecular docking used AutoDock Vina, while ligand visualization and receptor binding used PyMOL(TM) 1.7.4.5.Edu. The receptor used was HMG-CoA reductase (PDB code: 1HWK) with atorvastatin as a control ligand. Catechin, schisandrin B, and CHEMBL216163 had the highest inhibition with affinity energies of -7.9 kcal/mol, -8.2 kcal/mol, -8.3 kcal/mol, respectively. Amino acid residues that played a role in ligand and receptor interactions were Ser684, Asp690, Lys691, Lys692.